Environmental security and resilience Indonesia and global challenges - Kathryn A. Monk; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2022)
Indonesia faces tremendous challenges from climate change, biodiversity loss, and wider social and economic change. These challenges need extensive interdisciplinary approaches enabling multiple perspectives from diverse stakeholders to be recognised and utilised. Collaboration between scientists, social scientists, and economists has never been so important. As  Christiana Figueres, former Executive Secretary, United Nations Framework Convention on Climate Change said:  The [global] challenges we face are massive, urgent, and interconnected. We need people across all sectors to pull together and move us to a bright and strong future. Theres no time to waste!â€.  We are therefore happy to see the growing number of community-based participatory studies being submitted to InJAST and hope these will increase in future. There are exciting and vitally important issues to be tackled and supported by environmental managers to build the necessary environmental security and resilience, from direct conservation work to flood risk management and pollution control. Climate change drives or affects all these of course and has been, for example, one of the key drivers for Indonesias momentous plans to move the capital from the 256,000-hectare (990-square-mile) Jakarta on the north-western side of Java Island, the most populated island in the country, to the relatively undeveloped and biodiversity-rich East Kalimantan province on the island of Borneo. Climate change and immediate economic drivers in many parts of Indonesia also contribute to the annual toxic haze, which causes air quality to reach hazardous levels and creates major health, environmental and economic problems, especially in Sumatra and Java. Indeed, as of March this year, Riau province has already declared a state of emergency ahead of this years main fire season.